Angiotensin II enhances thrombosis development in renovascular hypertensive rats - Mogielnicki, Andrzej; Chabielska, Ewa; Pawlak, Robert; Szemraj, Janusz; Buczko, Wlodzimierz (Thrombosis and Haemostasis, 2005)
There is an increased number of in vitro evidence that angioten-sin II (Ang II) may promote thrombosis. However there are no in vivo experiments exploring the effect of Ang II on thrombus formation. In the present study we have investigated the influence of Ang II on venous thrombosis in renovascular hypertensive rats. Furthermore, we examined the role of AT1 receptor and Ang II metabolites: angiotensin III (Ang III) and angioten-sin IV (Ang IV) in the mechanisms of Ang II action. The contribution of coagulation and fibrinolytic systems in the mode of Ang II action was also determined. Venous thrombosis was induced by ligation of vena cava. Ang II infused into rats developing venous thrombosis caused dose-dependent increase in thrombus weight, which was partially reversed by losartan, selective AT1 antagonist. Ang III did not influence the thrombus formation in hypertensive rats, while Ang IV caused a marked increase in thrombus weight only in one of the used doses. Our study shows that Ang II via AT1 receptor enhances thrombosis development. The prothrombotic effect of Ang II may partially depend on enhanced leukocytes adhesion to endothelial cells accompanied by accelerated fibrin formation and increased plasma level of PAI-1. Moreover, Ang II action is partially mediated by one of its metabolites – Ang IV.
Keywords: Angiotensin; hypertensive rat; haemostasis; venous thrombosis